(untitled) (Journal of Hama University, 2019)
The study aimed at identifing the histological changes caused by the Hydatid cysts of Echinococcus granulosus in sheep lung tissues. Ten Excluded lung samples Infected with the Hydatid cysts were collected. The pathological changes of the lungs were recorded. Lung hydrated cysts were taken out of the lungs and fixed in10% natural buffered formaldehyde. Macroscopically, it was observed that The lungs of the infected sheep were found to contain a cyst of several different sizes. It was noticed that some cysts were located within the lung tissue completely, and others were obvious on lung surface. It was found that the septal lung lobes were more affected. Generally, the Hydatid cysts filled with pure to partially turbid fluid. Its texture was either soft, doughy or hard. Histological changes were characterized by hyperemia of the pulmonary affected tissues. The alveoli especially near the Hydatid cysts wall was compression. There was thickening of the interstitial tissue due to an inflammatory reaction composed of lymphocytes, macrophages, and fibroblast cells. The inflammatory reaction was also observed around the wall of the Hydatid cysts in addition to connective tissue forming the cyst wall. Histologically the cyst layers were composed of a thin layer of epithelial cells containing brood capsules and capitula followed by a laminated layers and an external prickly layer.